Dampak Mutu Pelayanan Terhadap Kepuasan Pasien BPJS Rawat Jalan di Instalasi Farmasi Rumah Sakit - Maharani Putri Wibowo; Ihsanti Dwi Rahayu; Muhammad Fitra Wardhana (CV. ITTC INDONESIA, 2026)
Service quality in hospital pharmacy installations is a key determinant of patient satisfaction, especially among BPJS outpatient participants who represent the majority of public healthcare users. Issues such as long queues, limited drug availability, insufficient pharmaceutical staff, and poor communication between patients and pharmacy personnel significantly influence perceived service quality. This review aims to identify and categorize the factors affecting BPJS patient satisfaction with hospital pharmacy service quality through a systematic literature review. Articles were retrieved from Google Scholar and ScienceDirect using a combination of keywords and Boolean operators. Inclusion criteria consisted of original research articles, full-text availability, written in either Indonesian or English, and published between 2020 and 2025. Out of 757 articles found, 8 were selected based on topic relevance and data completeness. The findings indicate that service quality dimensions such as empathy, reliability, responsiveness, assurance, and physical evidence strongly influence patient satisfaction. Dissatisfaction was commonly associated with long waiting times, lack of staff, and drug unavailability, while fast, friendly, and informative services were shown to significantly improve patient satisfaction. Therefore, improving service quality should focus on strengthening human resources, enhancing facilities, and implementing continuous performance evaluations in pharmaceutical services.